Intraoperative Monitoring Cerebral Blood Flow During the Treatment of Brain Arteriovenous Malformations in Hybrid Operating Room by Laser Speckle Contrast Imaging - Sicai Tao; Tingbao Zhang; Keyao Zhou; Xiaohu Liu; Yu Feng; Wenyuan Zhao; Jincao Chen (Frontiers in Surgery, 2022)
BackgroundHemodynamic changes caused by hybrid surgery for brain arteriovenous malformations (bAVM) are usually related to long-term lesions from “blood stealing”. There are currently no viable low-cost, noninvasive procedures for assessing cerebral perfusion in the operating room. This study aims to investigate the use of intraoperative laser speckle contrast image (LSCI) software in AVM surgery.MethodsIn Zhongnan Hospital of Wuhan University, 14 patients who underwent surgery with LSCI were collected. To analyze the hemodynamic features of AVM and the influence on the peripheral cortex of AVM embolization and resection, we assessed the transit time between feeding arteries and drainage veins by intraoperative digital subtraction angiography (DSA). Meanwhile, LSCI was performed at pre-embolization, post-embolization, and after complete resection of bAVM.ResultsIn this study, the transit time of bAVM before and after embolization was compared, the transit time before embolization was significantly shorter than that after embolization (p < 0.05). We also got good visualization of relative CBF, in addition, to flow imaging in the cortical vasculature round bAVM with LSCI. The flux of post-surgery was significantly higher than pre-embolization (p < 0.01).ConclusionHemodynamic variable assessment plays an important role in the resection of AVM in the hybrid operative room and LSCI can be used to visualize and evaluate cortical cerebral blood flow to detect pathological hyperperfusion in real-time with a good spatial-temporal resolution in a sensitive and continuous, non-invasive mode.